(untitled) (Research, Society and Development, 2023)
This research aimed to analyze the vaccination coverage (CV) in children under two years of age in a municipality of the Baixada Maranhense. This is a descriptive research with a quantitative approach, using data collected in the Information System of the National Immunization Program (SI-PNI) regarding the vaccination coverage of children under two years of age in the municipality of Pinheiro - MA, in the period from 2017 to 2019. The data were tabulated in a spreadsheet in Excel 2016, version 1905. The variables were presented in absolute and relative numbers, in the form of a table. The results presented data regarding immunobiologicals: BCG, DTP, Yellow Fever, Hepatitis A, Hepatitis B, Meningococcal, Pentavalent, Pneumococcal, Polio, Human Rotavirus, Viral Tetra, Viral Triple. Therefore, it was observed that the municipality of Pinheiro - MA is vulnerable in relation to vaccination coverage for measles, mumps, rubella, hepatitis B, polio, among others, since the goals recommended by the Ministry of Health were achieved only for BCG and Hepatitis B in children under 30 days of life in 2018. The research was limited by the underreporting regarding childhood immunization in the period under analysis.